From technophobia to technophilia: The paradox of imagining the feminine persona of the Chinese AI assistant - Moch. Zainul Arifin; Heru Nugroho; Sugeng Bayu Wahyono (SIMULACRA: JURNAL SOSIOLOGI, 2026)
Artificial intelligence (AI) assistants, such as Apple's Siri, Amazon's Alexa, OpenAI's ChatGPT, and ByteDance's Cici, are increasingly incorporating feminine personas. Given Cici's popularity and its pronounced feminine persona, this study examines how Indonesian users imagine the Chinese AI assistant. Drawing on a thematic analysis of interviews with 23 participants, the study explores users' imaginaries and appropriations of Cici's feminine persona. The findings suggest that the feminine persona of AI assistants serves as a means of domesticating AI. Initial anxieties about AI technology, often perceived as capable of replacing humans, contribute to technophobia (fear of technology), but Cici's feminine persona tends to alleviate it. This article argues that the transition from technophobia to technophilia (love of technology) is non-linear due to the intertwining of technological and gender imaginaries. This dynamic produces the paradox of imagining Cici: the paradox of belonging and the paradox of equality. On the one hand, users feel ownership, equality, and control over Cici. On the other hand, their behavioral data may be extracted by platforms, reinforcing existing gender inequalities. Thus, imaginaries of AI are not universal but are instead shaped by specific sociocultural contexts, calling for greater attention to Global South perspectives.